Answer:
(x-1)^2+(y+19/8)^2=2665/64
Step-by-step explanation:
The general equation of a circle is
(x - h)^2 + (y - k)^2 = r^2
Substituting the values of the 3 given points:
(-5 - h)^2 + (0 - k)^2 = r^2
(0 - h)^2 + (4 - k)^2 = r^2
(2 - h)^2 + (4 -k)^2 = r^2
Subtracting the second equation from the first:
(-5-h)^2 - h^2 + k^2 - (4 - k)^2 = 0
25 + 10h + h^2 - h^2 + k^2 - 16 + 8k - k^2 = 0
10h + 8k = -9 ------------ (A).
Subtract the third equation for the second:
h^2 - (2 - h)^2 + 0 = 0
h^2 - 4 + 4h - h^2 = 0
4h = 4
h = 1.
Substituting for h in equation A:
10 + 8k = -9
8k = -19
k = -19/8
So r^2 = (-5-1)^2 + (0 + 19/8)^2 =
36 + 361/ 64
= 2665/64